The picky men: Men's preference for women's body differed among attractiveness, health, and fertility conditions. (February 2023) - Han, Chengyang; Li, Xiangqian; Wang, Shuai; Hong, Ranran; Ji, Jiajia; Chen, Jixu; Zhu, Haoliang; Morrison, Edward R.; Lei, Xue
Abstract: The health and fertility hypothesis suggests that low body weight young women are healthy and fertile, thereby judged as attractive to men. Although it has been widely accepted, few studies have tested the health and fertility hypothesis on a perceptual level, that is whether the most attractive female body is also perceived as the healthiest and most fertile. In the current study, we investigated young and older men's preferences women's body weight, using 3D human body models. With an interactive body preference task, men chose the BMI and body fat of women's body shapes perceived as most attractive, healthiest and most fertile. The results showed that both young and older men had similar patterns of preferences for women's bodies. For BMI, the most attractive body weight was not seen as the healthiest or the most fertile. Compared to the most attractive BMI, higher BMI was required to be seen as the healthiest and this figure was even higher for fertility judgements. Body fat generally showed similar patterns of results as BMI. Our findings challenge the health and fertility hypothesis and point to the alternative explanation that the judgement of women's attractiveness tracks cues indicating youth and low parity. Highlights: Women with low BMI and BF judged as attractive are not seen as healthy and fertile. Relatively higher BMI and BF is required to be seen as healthy and fertile in female bodies. The judgement of women's attractiveness may track cues indicating youth and low parity, rather than health and fertility.